Implementasi Teknik Pernafasan Pursed Lips Breathing Dengan Teknik Tripoid Position Untuk Meningkatkan Saturasi Oksigen Pada Pasien Ppok Di Rumah Sakit TK II Putri Hijau Medan - Azmi Ihsan; Huwaina Af’idah; Erita Gustina (STIKES Columbia Asia Medan, 2025)
Chronic Obstructive Pulmonary Disease (COPD) is one of the leading causes of morbidity and mortality worldwide. One of the most common symptoms in COPD patients is shortness of breath. If this symptom persists, it can worsen the patient's condition, starting with decreased oxygen saturation (SpO2) and increased respiratory rate (RR), potentially leading to death depending on its severity. Therefore, management is required both pharmacologically and non-pharmacologically. Techniques such as pursed-lips breathing (PLB) and the tripod position have been proven to help improve breathing in COPD patients. This study aimed to implement PLB combined with the tripod position to improve oxygen saturation in COPD patients. The research employed a descriptive design using a case study approach on two patients hospitalized at TK II Putri Hijau Hospital Medan. The intervention was carried out over three days, three times per day, for 15-30 minutes each session. The results showed that on the first day, both cases had an oxygen saturation of 95%; on the second day, it increased to 97%; and on the third day, it further increased to 99%. Both patients demonstrated reduced use of accessory respiratory muscles, more effective respiratory rates, and improved oxygen saturation. These findings indicate that the combination of pursed-lips breathing and the tripod position effectively improves oxygen saturation in COPD patients. This study also suggests that these techniques can serve as recommended non-invasive nursing interventions in healthcare settings.